(untitled) (Journal of Partial Differential Equations, 2020)
We study logarithmic gradient estimate to smooth admissible solutions of the Hessian-type equations on S^n. The equations contain a Monge-Ampère equation arising in designing a reflecting surface in geometric optics as a special case.